Analisis wacana kritis Norman Fairclough terhadap bahasa slogan aksi demonstrasi guru di Samarinda - Rinda Cahya Mudiawati; Yusak Hudiyono; Bibit Suhatmady (Universitas Mulawarman, 2023)
This research discusses the great turmoil that occurred in October 2022 in the education environment of Samarinda City regarding the issue of removing teacher incentives. Thousands of teachers carried out demonstrations using written language contained in slogans. Slogans were used to protest against the circular letter from the Mayor of Samarinda concerning the alignment of incentives for teachers and education personnel. Critical discourse analysis was conducted to understand the meaning of the written language in the demonstration's slogan. Observation techniques, unstructured interviews, and photo documentation were also used as supporting methods in data collection. The research uses Norman Fairclough's three-dimensional analysis, which uses three main dimensions: the text, discourse, and social practice. This three-dimensional analysis can provide a more comprehensive and critical understanding of slogan language in a broader social, political, and cultural context. It can help reveal the power, meaning, and social implications of slogans and understand how slogans influence action and change in society.